Respon Air Perasan Ubi Jalar Ungu (Ipomoea Batatas L. Poiret) Pada Pakan Terhadap Peningkatan Warna Ikan Komet (Carassius Auratus) - Jaziroh Rizky Wulandari; Sri Oetami Madyowati; Maria Agustini; Achmad Kusyairi (Universitas Trunojoyo Madura, 2023)
Comet fish (Carassius auratus) is a freshwater ornamental fish which is quite well known among the public. The attractiveness of ornamental fish can be measured by its brilliant color, shape, physical fitness, behavior and state of health or stamina. Purple sweet potato (Ipomoea batatas L. poiret) has high antioxidant compounds, in addition to the anthocyanins present in sweet potatoes, vitamin C, vitamin E, lutein, zeaxanthin, and Î²-carotene which are carotenoid antioxidant pairs. This study aims to determine the increase in the color of koi fish after being given artificial feed added purple sweet potato. The method used in this study was an experimental method with a completely randomized design consisting of 4 treatments, tested for 30 days. The comet fish used were 2-3 months old and 5-6 cm in size. From the results of the study, the addition of purple sweet potato juice to the feed had an effect on increasing the color of comet fish whereas treatment C with a dose of 50 ml resulted in an increase in comet fish color with the highest average of 28, 53 RGB.